2011
DOI: 10.1007/s13157-011-0162-y
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Arbuscular Mycorrhizal Symbiosis in the Distribution of Sawgrass and Cattail in Florida Everglades

Abstract: In areas of the Florida Everglades, USA, a massive replacement of the historically predominant sawgrass by native cattail is occurring. Phosphorus enrichment due to runoff and hydrological engineering is considered a major environmental cause. As part of our investigation into the genetic and molecular mechanisms underlying this habitat shift, we examined the possible involvement of arbuscular mycorrhizal (AM) symbiosis in sawgrass and cattail. Laboratory experiments determined that sawgrass, but not cattail, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
(93 reference statements)
0
6
0
Order By: Relevance
“…All seeds were sown on medium containing 100 mM phosphate (Pi, in the form of KH 2 PO 4 ), pH 6.5, under a 16L : 8D photoperiod (average irradiance of 250 mmol quanta m Ϫ2 s Ϫ1 Gro-Lux fluorescent light) and a 25ЊC day/15ЊC night temperature regime in a growth chamber. The medium was prepared according to modified Hoagland formulation as described in detail in Lin et al (2011) and solidified with phosphorus-free Phytagel (Sigma, St. Louis, MO) at 2.7 g L Ϫ1 . Seeds germinating within a 1-wk window were considered cohorts.…”
Section: Seed Germination and Plant Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…All seeds were sown on medium containing 100 mM phosphate (Pi, in the form of KH 2 PO 4 ), pH 6.5, under a 16L : 8D photoperiod (average irradiance of 250 mmol quanta m Ϫ2 s Ϫ1 Gro-Lux fluorescent light) and a 25ЊC day/15ЊC night temperature regime in a growth chamber. The medium was prepared according to modified Hoagland formulation as described in detail in Lin et al (2011) and solidified with phosphorus-free Phytagel (Sigma, St. Louis, MO) at 2.7 g L Ϫ1 . Seeds germinating within a 1-wk window were considered cohorts.…”
Section: Seed Germination and Plant Growthmentioning
confidence: 99%
“…In contrast to sawgrass, cattail is known to have greater tolerance to water depth, a high ability to occupy space, easy seed dispersal by wind/water and rapid seed germination, and apparent lack of arbuscular mycorrhizal symbiosis (McNaughton 1966;Krattinger 1975;Davis 1991;Weisner and Miao 2004;Miao 2004;Webb et al 2009;Lin et al 2011). These traits may help its rapid expansion into the sawgrass habitat when nutrient resources such as P become more available.…”
Section: Introductionmentioning
confidence: 99%
“…Alarcón and Cuenca (2005) stated that AMF improves environmental stress tolerance, enhances nutrient uptake, and aids in water absorption. Cladium jamaicense is efficient in acquiring and using nutrients in a nutrient-poor phosphate environment by secreting phosphatase, by conservation and recycling nutrients, and by a mutualistic association with AMF (Brix et al, 2018;Lin, Webb, and Zhang, 2011). Jayachandran and Shetty (2003) reported AMF in sawgrass peat-marl substrates in Florida.…”
Section: Mycorrhizamentioning
confidence: 99%
“…Most native plants thrive in the presence of AM fungi ( Aziz et al, 1995 ) which have also been responsible for altering the soil community structure ( Aziz et al, 1995 ) by unknown mechanisms. It was shown in California and Florida that native plants rely more on AMF than non-native plants ( Vogelsang et al, 2005 ; Lin et al, 2011 ). Native plants showed an AMF growth response of 82% greater than that seen in non-native species ( Vogelsang et al, 2005 ).…”
Section: Plant Invasion Mechanisms Of Brazilian Pepper Treementioning
confidence: 99%
“…The symbiosis between AMF and plants through unknown mechanisms may also activate the expression of plant genes required for uptake of inorganic phosphorous, nitrogen and other nutrients from depleted soils. Lin et al (2011) showed that the infection of sawgrass ( Cladium jamaicense ) in the Florida Everglades with AMF initiated the activation of a phosphate transfer gene which allowed the uptake of Pi from soil. It is quite plausible that invasive plants such as BP alter the soil microbial community much more significantly than is currently known.…”
Section: Plant Invasion Mechanisms Of Brazilian Pepper Treementioning
confidence: 99%